Ringing the changes in Europe regulatory competition and the transformation of the State ; Britain, France, Germany ; [with 18 tables] - Windhoff-Héritier, Adrienne 1944-; Knill, Christoph 1965-; Mingers, Susanne (<<de>> Gruyter, 1996)
The nature of state activities is undergoing rapid transformation in Europe. The European Union exerts influence on state practices in member countries, which in their turn shape European policy. In short, the Joint supranational policy-making framework and the development towards an integrated market have provoked a mutual, ongoing process of transformation between member states and European institutions. The future of institutional and policy innovation is gradually taking shape. How and why is this change taking place in the European Union? What are the underlying mechanisms and motive forces and how do they affect European policy? How does European legislation influence policy content, institutions, and relations between the state and society in member countries? These questions are examined with reference to a specific regulatory area, clean-air policy, in the interaction between strategies in Britain, France and Germany.
Literaturverz. S. 347 - 363. - Dt. Ausg. u.d.T.: Die Veränderung von Staatlichkeit in Europa
Keywords: Europäische Union; Industriepolitiek; Luchtverontreiniging; Overheidsbeleid; Politik; Recht; Air quality management -- Government policy -- European Union countries -- Case studies; Air -- Pollution -- Law and legislation -- European Union countries -- Case studies; Competition -- Government policy -- European Union countries -- Case studies; Industrial policy -- European Union countries -- Case studies; Internationaler Vergleich; Regulierung; Luftreinhaltepolitik; Europäische Union. Mitgliedsstaaten; Frankreich; Deutschland; Großbritannien; Fallstudiensammlung